K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

10 giờ trước (15:08)

\(\dfrac{43}{25}=\left(\pm\sqrt{\dfrac{43}{25}}\right)^2\)

13 giờ trước (11:43)

43/25 = (√43/5)² hoặc (-√43/5)²

7 tháng 3 2020

\(A=\frac{35}{42}+\frac{1}{12}+\frac{8}{12}+\frac{12}{42}+\frac{1}{25}+\frac{3}{12}-\frac{5}{42}\)

\(A=\left(\frac{35}{42}+\frac{12}{42}-\frac{5}{42}\right)+\left(\frac{1}{12}+\frac{8}{12}+\frac{3}{12}\right)+\frac{1}{25}\)

\(A=1+1+\frac{1}{25}\)

\(A=2+\frac{1}{25}\)

\(A=\frac{51}{25}\)

19 tháng 4 2019

\(\frac{3}{x}+\frac{4}{3}=\frac{5}{6}\)

\(\frac{3}{x}=\frac{5}{6}-\frac{4}{3}\)

\(\frac{3}{x}=\frac{-1}{2}\)

\(\Rightarrow3.2=\left(-1\right).x\)

\(\Rightarrow6=\left(-1\right).x\)

\(\Rightarrow x=6:\left(-1\right)\)

\(\Rightarrow x=-6\)

19 tháng 4 2019

\(\frac{x}{2}-\frac{2}{y}=\frac{1}{2}\)

\(\Rightarrow\frac{x}{2}-\frac{1}{2}=\frac{2}{y}\)

\(\Rightarrow\frac{x-1}{2}=\frac{2}{y}\)

\(\Rightarrow\hept{\begin{cases}x-1=2\\2=y\end{cases}\Rightarrow}\hept{\begin{cases}x=3\\y=2\end{cases}}\)

\(b,\frac{3}{x}+\frac{4}{3}=\frac{5}{6}\)

\(\Rightarrow\frac{3}{x}=\frac{5}{6}-\frac{4}{3}\)

\(\Rightarrow\frac{3}{x}=\frac{5}{6}-\frac{8}{6}\)

\(\Rightarrow\frac{3}{x}=\frac{-3}{6}\)

\(\Rightarrow x\cdot(-3)=18\Rightarrow x=-6\)

2 tháng 4 2019

1)

a)

\(\frac{-5}{6}.\frac{120}{25}< x< \frac{-7}{15}.\frac{9}{14}\)

\(\frac{-1}{1}.\frac{20}{5}< x< \frac{-1}{5}.\frac{3}{2}\)

\(\frac{-20}{5}< x< \frac{-3}{10}\)

\(\frac{-40}{10}< x< \frac{-3}{10}\)

\(\Rightarrow Z\in\left\{-4;-5;-6;-7;-8;-9;-10;...;-39\right\}\)

2 tháng 4 2019

\(\left(\frac{-5}{3}\right)^3< x< \frac{-24}{35}.\frac{-5}{6}\)

\(\frac{25}{3}< x< \frac{-4}{7}.\frac{1}{1}\)

\(\frac{-25}{3}< x< \frac{-4}{7}\)

\(\frac{-175}{21}< x< \frac{-12}{21}\)

\(\Rightarrow Z\in\left\{-13;-14;-15;-16;...;-174\right\}\)

27 tháng 6 2017

\(-x-\frac{3}{4}=-\frac{8}{11}=>-x=-\frac{8}{11}+\frac{3}{4}=\frac{1}{44}=>x=-\frac{1}{44}\)

27 tháng 6 2017

-x-3/4=-8/11

=0.02272727....

11/12-(2/5+x)=2/3

=-0.15

6 tháng 8 2019

a,\(\frac{1}{x-1}+\frac{-2}{3}.\left(\frac{3}{4}-\frac{6}{5}\right)=\frac{5}{2-2x}\)

\(\Rightarrow\frac{1}{x-1}+\frac{-2}{3}.\left(\frac{3}{4}-\frac{6}{5}\right)=\frac{5}{2-2x};Đkxđ:x\ne1\)

\(\Rightarrow\frac{1}{x-1}+\frac{-2}{3}\left(\frac{-9}{20}\right)=\frac{5}{2-2x}\)

\(\Rightarrow\frac{1}{x-1}+\frac{3}{10}=\frac{5}{2-2x}\)

\(\Rightarrow\frac{1}{x-1}-\frac{5}{2-2x}=\frac{-3}{10}\)

\(\Rightarrow\frac{1}{x-1}-\frac{5}{-2\left(x-1\right)}=\frac{-3}{10}\)

\(\Rightarrow\frac{1}{x-1}+\frac{5}{2\left(x-1\right)}=\frac{3}{10}\)

\(\Rightarrow\frac{7}{2\left(x-1\right)}=\frac{-3}{10}\)

\(\Rightarrow70=-6\left(x-1\right)\)

\(\Rightarrow6x=6-70\)

\(\Rightarrow6x=-64\)

\(\Rightarrow x=\frac{-32}{3}x\ne1\)